Interference: Its Role in the Target Language Mastery to Indonesian Learners - Win Listyaningrum Arifin (UIN Salatiga, 2011)
In terference form one language to target language is something that cannot be denied. This paper discusses about the notion of interference, interference and second or foreign language learning, interference and communication, interference and Indonesian learners and its process. In the interference, there are negative transfer that which leads to an error or inappropriate form in the target language and positive transfer that makes the learning easier. Furthermore, during the language communication, native language can influence target language and the like. Thus, interference in communication can be: (1) influence of language contact experienced by bilingual or multilingual person; (2) language infiltration that influence the system to both target and native language, causing negative effect; (3) personal utterances in a narrow space as a parole effect (speech). In addition, interference to Indonesian learners can be in the area of phonology, morphology, sentence, and semantics.Keywords;Interference; Second or Foreign Language Learning; Indonesian Learner